Benthic-pelagic mixing of trace elements in estuarine food webs. (January 2022) - O'Mara, Kaitlyn; Fry, Brian; Burford, Michele
Abstract: Trace element accumulation pathways are important in many ecological and toxicological studies on aquatic organisms, yet these pathways are often poorly understood. To study the influence of diet and environment on the trace element composition of species within estuarine food webs, we performed a community level assessment of 28 trace elements (including major and minor elements) in common fish and prawn taxa across four estuaries, and in fish, prawn, and other invertebrate taxa within a single estuary. Despite sediment substrates from the four estuaries having distinctly different geochemical compositions, food web samples showed no separation by estuary, but clear separation by taxa. Grouping of taxa by trace elements was related to feeding ecology, with pelagic taxa separated from benthic taxa, and mixed feeding by generalist taxa. Arsenic and selenium were more concentrated in benthic fish, while aluminium, barium, copper, iron, manganese, vanadium, and zinc were more concentrated in pelagic fish. Trophic level did not appear to influence trace element composition. Previous laboratory studies have shown that food sources influence trace element concentrations in marine taxa and this study confirms that this also occurs in natural food webs. These results improve our understanding of the dominant importance of diet and physiology in controlling the trace element composition of species within estuarine food webs. Highlights: We performed a community level assessment of trace elements in estuarine food webs. Estuaries were geochemically distinct. Animals did not match sediments but were grouped by taxa. We identified a benthic-pelagic mixing gradient of trace elements across taxa. Our results provide new insights into broad scale trace element accumulation.